The Measurement of Soil Erosion and Run-off an Attempt and Some Results - Gorrie, R. Maclagan (Indian Forester, 1937)
Examples are given of soil erosion and run-off data actually measured In the U. S. A. ; the type of apparatus used in these experiments is described and some of the difficulties discussed. The first attempts at evolving a similar apparatus for Indian conditions are described. Data so far collected are given, but merely as an indication of the types of error which are to be expected. The Punjab Irrigation Research Institute has collected these figures while reducing the measurements to a standard routine, so that the next step, namely the measurement of erosion on various types of land, can be undertaken with some guarantee of precision.